Highly efficient oxygen photosensitization of carbon dots: the role of nitrogen doping. Issue 9 (24th February 2020) - Wu, Shihong; Zhou, Ronghui; Chen, Hanjiao; Zhang, Jinyi; Wu, Peng
Abstract : The role of nitrogen doping in the highly efficient oxygen photosensitization of carbon dots is underlined. Abstract : Photosensitization is a promising avenue of oxygen activation, which can overcome the spin selection rule to transform the ground state oxygen ( 3 O2 ) into a highly reactive singlet oxygen ( 1 O2 ). Carbon dots (CDs) are a promising type of carbon-based photosensitizer, and nitrogen doping can further improve the oxygen photosensitization performance. Although the roles of nitrogen doping in tuning the optical properties (mainly absorption and fluorescence) of CDs have been well-studied, their association with oxygen photosensitization has not been reported. Herein, using the well-developed synthetic protocol of hydrothermal treatment of citric acid and ethylenediamine, we prepared nitrogen-doped CDs (N-CDs) of varied nitrogen contents. The oxygen photosensitization performances of the N-CDs were first confirmed by ROS investigation with TMB oxidation as the ROS probe and EPR. After XPS analysis of the surface nitrogen doping speciation, it was found that the changes of graphitic N and pyrrolic N correlated well with the oxygen photosensitization performances of N-CDs. Further theoretical calculations indicated that the two key factors for oxygen photosensitization, namely triplet activation and oxygen adsorption, are mainly associated with graphitic N and pyrrolic N, respectively. The results in this work help further understanding of the oxygen photosensitization mechanism of N-CDs, and are expected to be useful in the future design of carbon-based photosensitizers.